Water Status Detection Method Based on Water Balance Model for High-Power Fuel Cell Systems - Yiyu Zhong; Yanbo Yang; Naiyuan Yao; Tiancai Ma; Weikang Lin (Energies)
With the gradually accelerating pace of global decarbonization, highly efficient and clean proton exchange membrane fuel cells (PEMFCs) are considered to be an energy solution for the future. During the operation of a fuel cell, it is necessary to keep the internal proton exchange membrane in a good state of hydration, so an appropriate method of detecting the hydration state is essential. At present, fuel cell systems are rapidly developing towards high power, but methods for detecting the hydration state of high-power fuel cell systems are still relatively lacking. Therefore, this paper studies the hydration state of high-power fuel cell systems and builds a condensation tail-gas water collection device for calculating the water flow out of a fuel cell system, deriving the hydration status inside the high-power fuel cell system. To verify the proposed water balance model, a series of experiments were conducted based on controlled variables such as working temperature, air metering ratio, and load current. Experiments were conducted on a 100 KW fuel cell system to collect water flow from the fuel cell system. Finally, based on the experimental data, the change rate of the internal water content of the fuel cell system under different conditions was calculated. The results show that, under the same load current, as the working temperature and air metering ratio increase, the change rate of the internal water content of the fuel cell system gradually decreases. Therefore, at low power, it is necessary to maintain an appropriate working temperature, while at high power, maintaining an appropriate air metering ratio is more important.